KONSEP HAK DALAM PEMIKIRAN FIQH HANAFIYAH SERTA TRANSFORMASINYA DALAM UNDANG-UNDANG HUKUM PERDATA TURKI MODERN - Tohari, Chamim (Ahkam: Jurnal Hukum Islam, 2018)
ABSTRACTThis study disscuss the concept of right in the Hanafiâs fiqh books. The Hanafiâs thought was chosen as the object of this study because the discussion on thought of right is written more in the Hanafiâs literatures. The major problems which is discussed in this study are: (1) How is the concept of right and its application in the Hanafiâs fiqh school? (2) How is the relevance about the concept of right in the Hanafiâs school to the Turkish modern private law? This study is a library research with the content analysis method. The finding confirms that First, the terminology of right in the Hanafiâs fiqh school is more interpreted in the conection to the ownership of a property. In the Hanafiâs thought, the right is defined as a freedom or a special authority to use a thing according to the law. Then, the application ot the concept of right in the Hanafi school using several principles as (1) The application of concept of right cannot contradict to the Qurâan and Sunnah; (2) The utilization of right is permissible as long as it does not cause danger or loss to the owner and to the other; and (3) The utilization of right must be oriented to the benefit and avoid an invain and profuse by the owner. Second, the Turkish modern private law has a relevance with the Hanafiâs thought in relation to the right arrangements problem for its citizen. Based on several proofs which were discovered in this research, it can be concluded that the concept of right of the Hanafiâs thought had been transformed in the Turkish modern private law. The contribution which is expected from this study is the development of concept of right which may be applied to solve many contemporary problems in the field of Islamic economy.Keywords: Hak, Properti, Tasarruf, Fiqh Hanafiyah, Hukum.